Disunity, Distance, Disregard: The Political Failure of Islamism in Late Colonial Indonesia - Elson, Robert E. (Studia Islamika, 2009)
This article examines the failure of Islamism to make a greater political impact in Indonesia through these years. That failure would have decisive ramifications for the future shape of the Indonesian state, in that it left Islamism politically and intellectually impoverished and politically marginalized in the face of the dominant claims of pseudo-secular nationalists. In part, its failure flowed from organizational and administrative weakness, but it was centrally rooted in the strategic, political and intellectual shortcomings of Islamist politicians'. That opportunity was never taken up effectively. For the most part, the list decade or so of the colonial period witnessed Islamism's intellectually unsophisticated, internally divided and counter-productive efforts to progress its agendaDOI:Â 10.15408/sdi.v16i1.488